Key Process Conditions for Production of C(4) Dicarboxylic Acids in Bioreactor Batch Cultures of an Engineered Saccharomyces cerevisiae Strain - Zelle, Rintze M. (American Society for Microbiology (ASM), 2010)
A recent effort to improve malic acid production by Saccharomyces cerevisiae by means of metabolic engineering resulted in a strain that produced up to 59 g liter(−1) of malate at a yield of 0.42 mol (mol glucose)(−1) in calcium carbonate-buffered shake flask cultures. With shake flasks, process parameters that are important for scaling up this process cannot be controlled independently. In this study, growth and product formation by the engineered strain were studied in bioreactors in order to separately analyze the effects of pH, calcium, and carbon dioxide and oxygen availability. A near-neutral pH, which in shake flasks was achieved by adding CaCO(3), was required for efficient C(4) dicarboxylic acid production. Increased calcium concentrations, a side effect of CaCO(3) dissolution, had a small positive effect on malate formation. Carbon dioxide enrichment of the sparging gas (up to 15% [vol/vol]) improved production of both malate and succinate. At higher concentrations, succinate titers further increased, reaching 0.29 mol (mol glucose)(−1), whereas malate formation strongly decreased. Although fully aerobic conditions could be achieved, it was found that moderate oxygen limitation benefitted malate production. In conclusion, malic acid production with the engineered S. cerevisiae strain could be successfully transferred from shake flasks to 1-liter batch bioreactors by simultaneous optimization of four process parameters (pH and concentrations of CO(2), calcium, and O(2)). Under optimized conditions, a malate yield of 0.48 ± 0.01 mol (mol glucose)(−1) was obtained in bioreactors, a 19% increase over yields in shake flask experiments.